Associations between adolescents’ physical activity behavior and their perceptions of parental, peer and teacher support - Beata Pluta (Archives of Public Health, 2020)
Abstract Background The aim of this study was to examine adolescents’ perceptions of parental, teacher, and peer support for physical activity, and to examine the associations between these perceptions and physical activity behavior. Methods The study included 902 secondary school students, who completed the Short Scale of Youth’s Social Support Assessment (SSYSS). The level of physical activity – more specifically, moderate to vigorous physical activity – was measured using a Physical Activity Screening Measure. The associations were examined by a five-step hierarchical regression. Body mass index (BMI) was defined using the LMS method, which summarizes the distribution of BMI by age and gender in terms of three curves, L (lambda), M (mu), and S (sigma), and was based on a nationally representative sample of Polish children and adolescents. Results The study indicated a positive correlation between MVPA (moderate to vigorous physical activity) and three sources of social support; however, in the regression model, this explained only part of the variance. In the hierarchical multiple regression analysis, MVPA level was predicted by five variables involvement in sports training, teachers support, parents support, gender and BMI. The direct effects for teachers and parents support were similar. This demonstrates that both teachers’ and parents’ social support exert influence on adolescent MVPA. Conclusions The findings from this research suggest that school-based interventions for adolescents should specifically take into consideration family, teachers, and peers as important sources of social support for general physical activity promotion that aims to increase its levels.